Case report on toxicity of methotrexate in tubal ectopic pregnancy - Lodha, Surbhi; Mali, Kimaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ectopic pregnancy is defined as pregnancy outside uterine cavity. Of all ectopic pregnancy, tubal ectopic is most common. Most cases today are diagnosed early and hence timely treatment is possible. In stable patients, medical line of management with methotrexate can be used. With early diagnosis and medical line of treatment, use of injectable methotrexate is on rise. Being aware of characteristics of methotrexate like mechanism, dosage, side effects and contraindications, appropriate patient selection and watchful monitoring will help reduce methotrexate induced toxicity.